Analysis of the presence and location of mast cells in periapical cysts and periapical granulomas - NOGUEIRA,Emerson Filipe de Carvalho (2016)
ABSTRACT Objective: The aim of the present study was to locate mast cells in chronic periapical lesions (granulomas and cysts) by using histochemical techniques and toluidine blue staining. Methods: A quantitative, descriptive, cross-sectional and retrospective research was performed. The sample was obtained from histopathological reports in the archives of the laboratory of surgical pathology of the University of Pernambuco between November 2014 and May 2015. Results: Sixteen cases of granuloma and 21 cases of periapical cysts were selected. The stained slides were analyzed by two examiners at different times, in a double-blind study. Mast cells were found in 13 (61.9%) of the periapical cyst cases, located in the capsule of the lesion. In the periapical granuloma cases, mast cells were found in eight cases (50%), located in the granulation tissue. Conclusion: Mast cells were detected in both cysts and periapical granuloma, located in the capsule and granulation tissue, respectively. Mast cells were more prevalent in periapical cysts than in periapical granuloma.